Socio demographic factors to assess leucorrhoea in married women of reproductive age group in an urban slum community - Rajadhyaksha, Nikita G.; Kasbe, Abhiram M. (International Journal Of Community Medicine And Public Health, 2022)
Background: Reproductive health is a critical part of general health and reproductive tract infections create a major health problem in developing nations. Leucorrhoea is a common but difficult condition to treat due to its uncertain aetiology. A variety of factors put women at risk of these infections and socio demographic factors play a substantial role. The purpose of the study was to find the prevalence of leucorrhoea and socio demographic risk factors associated with it. Methods: A community based cross-sectional study of 350 women aged between 18-49 years residing in an urban slum of Mumbai, having white discharge for more than 2 weeks. Systematic random sampling used. Statistical analysis of the significance of association of different socio demographic variables was done. Results: The prevalence of leucorrhoea was found to be 66.9%. It was found to be 48% in women aged 23-32 years with predominance amongst the Muslim population (i.e.,74%) and those belonging to Socio-economic class 2 had a higher proportion (i.e.,74.4%). Education had miser influence on leucorrhoea. Conclusions: Routine screening and periodic surveys to detect the pattern of discharge are needed to understand the common problem of leucorrhoea and help initiate appropriate medical treatment and personal hygiene.